Sheep abortion – a roundtable discussion. (1st September 2021) - Crilly, JP; Carson, Amanda; Gascoigne, Emily; Griffiths, Bryan; Griffiths, Liz; Henry, Joseph; Hamer, Kim; Hovers, Kate; Lovatt, Fiona; Richey, Moyna
Abstract : Foreword: Abortion takes a heavy toll on the sheep industry, not only economically, but in emotional terms too. Enzootic abortion in ewes is consistently the most frequent diagnosis followed in descending order by infection with Toxoplasma gondii, Campylobacter spp., Salmonella spp. and Listeria spp. Causes of abortion also lead to increased barren rates, and the birth of weak lambs, so the impact of these pathogens is greater than just abortion. Fortunately there are vaccines for the two most common causes of abortion, providing farmers and the veterinary surgeons advising them with effective and sustainable tools in the control of enzootic abortion and toxoplasmosis. The uptake of these vaccines, however, remains lower than might reasonably be expected. In this roundtable discussion the barriers to the implementation of the extant measures of abortion control were discussed and suggestions made as to how abortion can better be prevented.